Factors associated with therapy noncompliance in type-2 diabetes patients Frecuencia y factores asociados al incumplimiento terapéutico en pacientes con diabetes mellitus tipo 2 - Lizbeth Hernández-Ronquillo; José Francisco Téllez-Zenteno; Juan Garduño-Espinosa; Erick González-Acevez (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To identify the frequency and factors associated with therapy noncompliance in type-2 diabetes mellitus patients. MATERIAL AND METHODS: A cross-sectional study was carried out in 79 patients with type-2 diabetes mellitus seen in major hospitals of Mexico City. Patients were visited at home, from March 1998 to August 1999, to measure compliance with prescribed therapy. Complying patients were defined as those taking at least 80% of their pills or 80% of their corresponding insulin dose. The degree of compliance with therapy components (diet, amount of exercise, and keeping appointments) was measured. RESULTS: The average age of study subjects was 59 years (SD 11 years); 73% (n=58) were female subjects. The overall frequency of noncompliance was 39%. Noncompliance rates were: 62% for dietary recommendations, 85% for exercise, 17% for intake of oral hypoglycemic medication, 13% for insulin application, and 3% for appointment keeping. Hypertension plus obesity was the only factor significantly associated with noncompliance (OR 4.58, CI 95% 1.0, 22.4, p=0.02). CONCLUSIONS: The frequency of therapy noncompliance was very high, especially for diet and exercise. OBJETIVO: Identificar la frecuencia y factores asociados al incumplimiento terapéutico en pacientes con diabetes mellitus tipo 2. MATERIAL Y MÉTODOS: Se llevó a cabo un estudio transversal en cuatro clínicas y hospitales de la Ciudad de México, en 79 pacientes con diabetes mellitus tipo 2. Se recolectaron datos sobre el cumplimiento terapéutico, para lo cual se visitó el domicilio de los sujetos de estudio entre marzo de 1998 y agosto de 1999, con el fin de contar los medicamentos. Se definió cumplimiento cuando el paciente administró correctamente 80% de las pastillas o de la dosis de insulina que le correspondía. Se midió el grado de cumplimiento para cada una de las medidas terapéuticas (dieta, ejercicio y asistencia a citas). RESULTADOS: La edad promedio del grupo fue de 59 años (DE=11 años); 58 pacientes (73%) fueron del sexo femenino. La frecuencia de incumplimiento global fue de 39%. La frecuencia de incumplimiento en el grupo donde se pudo llevar a cabo el conteo de medicamentos fue 62% para la dieta, 85% para el ejercicio, 17% para la administración de hipoglucemiantes, 13% para la aplicación de insulina y 3% para la asistencia a citas. Sólo la asociación de incumplimiento con la presencia de hipertensión arterial sistémica más obesidad fue estadísticamente significativa (RM= 4.58, IC 95%= 1.0-22.4, p= 0.02). CONCLUSIONES: La frecuencia de incumplimiento fue muy alta, especialmente en lo que se refiere a la dieta y al ejercicio.